5 Ideas to create engaging Google slides for teaching by using add-ons / Tuan Sarifah Aini Syed Ahmad - Syed Ahmad, Tuan Sarifah Aini (UiTM Cawangan Negeri Sembilan Kampus Seremban, 2021)
The COVID-19 pandemic has forced the closure of learning institutions at preschool, school and tertiary levels around the world. As a result, online learning has replaced the conventional and blended learning approaches. Therefore, educators have to create online learning activities and materials rapidly in order to replace the conventional learning activities or materials. There are many types of learning activities or materials used for teaching and learning. One type of the crucial materials is teaching slides which are used to provide learning contents. It is important to provide the learning content as teaching is about imparting knowledge to students. Since slides are now shared with students virtually, it is worthy to consider creating slides by using a cloud-based application such as Google Slides. Google Slides is a free web-based application provided by Google. The slides created using Google Slides are stored in the cloud system which is Google Drive. Before the pandemic, slides were mostly created by using PowerPoint. Your PowerPoint slides actually can be converted into Google Slides. Just upload the PowerPoint files in your Google Drive and save them as Google Slides as shown in Figure 1. The steps are very easy.